1993
DOI: 10.1007/bf01384746
|View full text |Cite
|
Sign up to set email alerts
|

African universities and the state: Prospects for reform in Senegal and Uganda

Abstract: Abstract. Uganda's Makerere University and the University of Dakar in Senegal were for many years after independence among Africa's premier universities. Today, their facilities have visibly deteriorated and the quality of instruction the institutions provide is seriously threatened -the consequence of political and economic turmoil combined with persistent underfunding. If higher education remains supply-driven without reference to available resources, the problems of Makerere and the University of Dakar can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Consequently, the higher education sector's ability to meet the national development needs of most of African countries such as Uganda through research, innovation and knowledge production is jeopardised (Collins & Rhoads, 2008;Eisemon & Salmi, 1993;Kibwika, 2006). Concern for how learning takes place in higher learning institutes and how instruction and assessment affect the quality of learning is desirable, because students need to acquire knowledge and skills that can be transferable in the workplace (Mikre, 2010;Mulder, 2014;Wesselink, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the higher education sector's ability to meet the national development needs of most of African countries such as Uganda through research, innovation and knowledge production is jeopardised (Collins & Rhoads, 2008;Eisemon & Salmi, 1993;Kibwika, 2006). Concern for how learning takes place in higher learning institutes and how instruction and assessment affect the quality of learning is desirable, because students need to acquire knowledge and skills that can be transferable in the workplace (Mikre, 2010;Mulder, 2014;Wesselink, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Universities have been very useful in providing the human resources needed to serve in public and private sectors worldwide (Elliots et al, 1996;Eisemon & Salmi, 1993). Even though the first university established in Cameroon had the mandate to provide a labour force to serve the demands of the newly independent nationCameroon (Njeuma et al, 1999); yet, many decades after independence, participants' responses revealed that university education in Cameroon is still being overwhelmingly regarded as a gateway to employment.…”
Section: University For Capacity Building and Employmentmentioning
confidence: 99%
“…Despite the timid and restricted start, several universities sprung up in Africa following independence and were faced with the mounting task of providing a labour force that would serve the Independent States (Eisemon & Salmi, 1993). Apart from having a mission to provide a labour force to serve the respective Independent States, newly established African universities were also charged to play a leading role in addressing the continent's outstanding problems of poverty, low production, hunger, unemployment, diseases and illiteracy (Mosha, 1986;Sawyerr, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the universities were both directly and indirectly controlled by the state in matters of admission and internal governance (Eisemon and Salmi, 1993). For example, the university chancellor was the head of the state, the vice-chancellors were direct appointees of the head of the state and the University Council and Board of Trustees were composed of senior civil servants and those close to the head of the state.…”
Section: Shift In University Outlook/modelmentioning
confidence: 99%